Nutrient Biofortification of microgreens (spinach) to combat hidden hunger (Journal of Agriculture and Biology, 2024)
Nutrient deficiency is a major cause of different health disorders in human beings. Malnutrition has become more alarming in under-developed countries and might affect more than 3 billion people in the world. Supplementation and food fortification of vegetable crops with minerals can address the issue of adequate nutrition security. Current study was focused to assess the nutritional status of vegetables after supplementation of different macro and micronutrients. The trial was conducted in growth room, Department of Horticulture, University of Layyah, Layyah. Seed of spinach was procured from a certified agency and directly sown in the trays (2 inches deep). This study employed a total of twenty four treatment conditions, comprising three distinct nutrient treatments (including Fe, Zn, and Ca) as well as a control treatment. Every nutrient was applied in three different concentrations following two application methods, constituting six treatments of individual nutrient. Each treatment was replicated three times, each replication containing 1 tray. The end produce was analyzed for different attributes like morphological parameters, biochemical parameters (Total soluble solids, Vitamin C, acidity, carotenoids, chlorophyll contents, lipophilic antioxidant (LPA), starch contents, amino acids, carotenoids, flavonoids, phenolic contents and ionic contents (Fe, Zn, and Ca) . Our results indicated that supplementation of 200ppm Zn, Fe @1.5mM and 200ppm calcium concentration is optimal for maintaining the normal growth of plants and to promote the major Zn, Fe and Ca concentration in the edible part of spinach. Thus, it could be proposed that the growth of spinach under 200ppm Zn, Fe @1.5mM and Ca @200ppm increased the intake of these nutrients and other beneficial compounds for the human health.